Performance and Exhaust Emission Characteristics of C.I Engine Using Biofuels and Its Diesel Blend with Nano-Additives - S. Jacob; L. Karikalan; J. Isaac JoshuaRamesh Lalvani; Aman Sharma; Maghalengam Kannappan (Advances in Materials Science and Engineering)
Depletion of fossil fuel assets makes it critical that we find biodiesel sources in the contemporary world. This work investigates dual bio-fuels of jatropha methyl ester and mahua methyl ester in various proportions, such as 15 : 5, 10 : 10, and 5 : 15. The performance and emission characteristics of JME15MME5, JME10MME10, and JME5MME15 blends of jatropha methyl ester and mahua methyl ester are suitable for diesel engines with little air pollution. Biodiesel blends with titanium dioxide nano-additives, such as jatropha methyl ester and mahua methyl ester, might be more efficient at the conclusion of the experiment, preserving fossil fuel assets for future generations. Performance parameters like BTE and SFC with different load conditions are analyzed for various blends, and then final results are drawn.